Explicit (Not Implicit) Attitudes Mediate the Focus of Attention During Sentence Processing - Horchak, Oleksandr V.; Garrido, Margarida Vaz (Frontiers in Psychology, 2020)
Many studies showed that comprehenders monitor changes in protagonists’ emotions and actions. This article reports two experiments that explored how focusing comprehenders’ attention on a particular property of the protagonist dimension (e.g., emotional or action state) affects the accessibility of information about target objects mentioned in the sentence. Furthermore, the present research examined whether participants’ attitudes towards the issues described in the sentence can modulate comprehension processes. To this end, we asked participants to read sentences about environmental issues that focused comprehenders’ attention on different mental and physical attributes of the same entities (protagonists and objects) and then self-report their own thoughts on the topic of environment by responding to the items assessing their environmental awareness. Importantly, we manipulated the task requirements across two experiments by administering a self-report task (Experiment 1), which required the participants to rate the seriousness and the frequency of the problem mentioned in a sentence; and administering a sentence-picture verification paradigm (Experiment 2), which required the participants to merely indicate if the object depicted in the picture (related to a certain environmental problem) was mentioned in the preceding sentence. The results of these experiments suggest that the focus of a sentence on the environmental problem (rather than the protagonist’s emotion and action) enhances the accessibility of information about environmental issues (e.g., plastic garbage); that the comprehender’s level of environmental awareness influences one’s attention during sentence processing; and that comprehender characteristics significantly modulate comprehension processes only when the measures tap into explicit (and not implicit) processes.